Approximation for Transient of Nonlinear Circuits Using RHPM and BPES Methods - H. Vazquez-Leal; K. Boubaker; L. Hernandez-Martinez; J. Huerta-Chua (Journal of Electrical and Computer Engineering)
The microelectronics area constantly demands better and improved circuit simulation tools. Therefore, in this paper, rational homotopy perturbation method and Boubaker Polynomials Expansion Scheme are applied to a differential equation from a nonlinear circuit. Comparing the results obtained by both techniques revealed that they are effective and convenient.